Stroke Hemorrhagic after Snakebite: A Scoping Review - Budi Rahayu, Ana; Yuniasih, Dewi; Sukirto, Novi Wijayanti; Hikmawan Yuliarto Benni Sambada, Taufiek; Selohandono, Andrianto (Ahmad Dahlan Medical Journal, 2024)
Snakebite envenomation is a neglected tropical disease that affects millions of individuals living in underdeveloped countries. Cerebral complications are often found in venomous snake bite victims. Certain snake venoms can interfere with the blood's ability to clot, increasing the risk of bleeding in the brain and potentially causing a stroke. previous literature review studies have not comprehensively reviewed stroke hemorrhagic after snake bites. Therefore, we are interested in conducting a literature review using the scoping review method on stroke hemorrhagic after snake bites. The samples in this study were published articles from international journals related to cerebral complications after snakebite that met the inclusion and exclusion criteria. The inclusion criteria used in this study were articles derived from the PubMed, ScienceDirect, and Scopus databases, using the keywords “Snakebite” OR “Snake envenoming” AND “Stroke hemorrhagic”. Based on the eligibility, Six articles were finally synthesized in the study. All of papers were a case report design. Three cases were from Brazil, three cases from Morocco, Burkina Faso and Togo. The snake that causes hemorrhagic stroke in Brazil is Bothropp spp. however, the type of snake in the instances from Burkina Faso and Morocco is unknown. There were a total of 10 instances reported from 6 journals. One patient from Morocco died, while another patient from Brazil suffered from prolonged hemiplegia. Furthermore, a total of 8 more patients were released from the hospital in an improved condition.